2002
DOI: 10.5483/bmbrep.2002.35.5.518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nordihydroguaiaretic Acid on the Secretion of Lipoprotein Lipase

Abstract: Nordihydroguaiaretic acid (NDGA), an inhibitor of lipoxygenase, inhibits the secretion of proteins and causes the redistribution of resident Golgi proteins into the endoplasmic reticulum (ER). In this study, the effect of NDGA on lipoprotein lipase (LPL) secretion was investigated in 3T3-L1 adipocytes, and compared with those of brefeldin A (BFA), a well-known fungal metabolite that exhibits similar ER-Golgi redistribution. Both BFA and NDGA blocked secretions of LPL. In the presence of BFA, the active and dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Prior work demonstrates that strongly activated mutants of FGFR3 actually recruit JAK1 directly to the ER leading to activation of STAT family members, which is not disrupted by brefeldin A (BFA) (18, 19). In our results reported here, we found that NDGA, an agent previously shown to disrupt the Golgi by mechanisms distinct from BFA (52), rapidly blocked activation of STAT1 and STAT3. Although NDGA possesses strong antioxidant activity, the effects of NDGA on FGFR3 activation and signaling were not attributable solely to antioxidant activity, as shown by the inability of a chemically unrelated antioxidant, Zileuton, to affect FGFR3 activation.…”
Section: Discussionsupporting
confidence: 70%
“…Prior work demonstrates that strongly activated mutants of FGFR3 actually recruit JAK1 directly to the ER leading to activation of STAT family members, which is not disrupted by brefeldin A (BFA) (18, 19). In our results reported here, we found that NDGA, an agent previously shown to disrupt the Golgi by mechanisms distinct from BFA (52), rapidly blocked activation of STAT1 and STAT3. Although NDGA possesses strong antioxidant activity, the effects of NDGA on FGFR3 activation and signaling were not attributable solely to antioxidant activity, as shown by the inability of a chemically unrelated antioxidant, Zileuton, to affect FGFR3 activation.…”
Section: Discussionsupporting
confidence: 70%
“…LPL plays a major role in TG metabolism and the efficiency or dysfunction of LPL has been found in association with the pathogenesis of hypertriglyceridemia (Bensadoun 1991). Previous studies have reported that a few agents increase LPL activity at transcriptional or post-transcriptional levels when added to adipocytes (Masuno and Okuda 1995;Kim et al 2002;Yang et. al.…”
Section: Introductionmentioning
confidence: 99%